An Unrecorded 1660 English Edition Of Michael Scot's Physionomia. (11th December 2019) - Stasevich, Vladislav
Abstract: This note is concerned with the possibly unique copy of a previously unknown 1660 edition of an English translation of Michael Scotus's Physionomia, which has survived in the holdings of the Library of the Russian Academy of Sciences. Though some records of this edition exist, none is properly bibliographical, and some bibliographers of the past have denied the existence of such a translation. The note offers a description of the particular copy, the make-up and content of the edition, the identity of the translator and a comparison of the translation with the Latin text of the editio princeps of 1477. The edition of 1660 is compared with two later English works from the eighteenth and nineteenth centuries which also purport to be the translations of the same work but in fact exploit the edition in question, progressively distorting it.